Persisting Corruption in Indonesia: Examining the Flaws in Political Party Financing - Putra, Fajar Surya (Journal of Public Administration and Policy Issues, 2023)
Corruption remains a persistent challenge in Indonesia, despite significant efforts by the Corruption Eradication Commission (KPK) to prosecute high-ranking politicians. The underlying issue fueling corruption is the flawed political party financing system, which creates vulnerabilities within the electoral process and governance. This paper examines three key aspects of political party financing that contribute to corruption: (1) the financial obligations imposed on election winners, (2) the inadequate political party subsidy system, and (3) the prevalence of illegal donations. The study highlights how financial pressures on political parties drive them to seek illicit funding sources, often leading to collusion with oligarchs and the misallocation of state resources. Additionally, political dynasties and regulatory loopholes further exacerbate corruption, undermining public trust in the government. The paper proposes solutions such as enhanced financial transparency, strict audit mechanisms, and state-funded political parties to reduce dependence on illicit funding. These reforms require a strong commitment from multiple stakeholders, including policymakers, law enforcement, and civil society, to restore democratic integrity and improve governance in Indonesia.